New insights into strange-quark hadronization measuring multiple (multi-)strange hadron production in small collision systems with ALICE - Pucillo Sara (EPJ Web of Conferences)
Among the most important results from the Run-1 and Run-2 of the LHC is the observation of an enhanced production of (multi-)strange to non-strange hadron yields, gradually rising from low-multiplicity to highmultiplicity pp and p–Pb collisions, reaching values close to those measured in peripheral Pb–Pb collisions [1]. The observed behaviour cannot be quantitatively reproduced by any of the available QCD-inspired MC generators. In this contribution an extension of this study is presented: the measurement of the Ks0, Λ, Ξ− and Ω− (together with antiparticles) multiplicity distributions in pp collisions at √s = 5.02 TeV as a function of the charged-particle multiplicity, together with the average probability for the multiplets production, extending the study of strangeness production beyond its average. This novel method, based on counting the number of strange particles event-by-event, represents a new test bench for production mechanisms, probing events with a large imbalance between strange and non-strange content.